(untitled) (International Journal of Food and Nutritional Sciences, 2021)
A preferred method for integrating numerous renewable energy sources into the network and running them concurrently is the energy management system. Controlling the energy dispersed across various distributed generators is crucial for the stable operation of the power system. The power of each individual generator in the specific DC network is controlled in this thesis work using a novel way based on the fall control technique. To achieve high energy distribution efficiency and also to increase stability, the suggested energy management system can be widely implemented to both the grid connected to the grid and the grid separated from the electricity grid Based on the drop control principle, an effective power control mechanism is created for dividing the power needed by the load. A single distributed generator can use the suggested controller to regulate its output power quickly and precisely. By modelling transient stability and steady state test tests, the power sharing control approach was developed, modelled, and validated. Additionally, the ideal coupling resistance for power sharing was found. Investigations into controller interface and communication lag were also conducted. The shared power controller experiences very little interference from communication delay. The MATLAB/SIMULINK environment is used to model the system.